2017
DOI: 10.1002/jcb.25977
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Structure of the Human Polyoma JC Virus Agnoprotein

Abstract: Agnoprotein is an important regulatory protein of the human polyoma JC virus (JCV) and plays critical roles during the viral replication cycle. It forms highly stable dimers and oligomers through its Leu/Ile/Phe-rich domain, which is important for the stability and function of the protein. We recently resolved the partial 3D structure of this protein by NMR using a synthetic peptide encompassing amino acids Thr17 to Gln52, where the Leu/Ile/Phe- rich domain was found to adopt a major alpha-helix conformation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…It was previously demonstrated that this protein is posttranslationally modified by protein kinases including protein kinase C (PKC) and cAMP-dependent kinase at the predicted phosphorylation sites at the "SRK, aa 7-9," "SVK, aa 11-13," "RKAS, aa 8-11," and "TKK, aa 21-23" (Johannessen et al, 2008;Sariyer et al, 2006). Agnoprotein also F I G U R E 3 The 3D structure of the full-length JC virus agnoprotein was recently resolved by NMR (Coric et al, 2017). According to this 3D structure, agnoprotein contains a minor and a major α-helix located at amino acid position Leu6-Lys13 and Arg24-Phe39, respectively.…”
Section: Functional Domains Of Agnoproteinmentioning
confidence: 99%
“…It was previously demonstrated that this protein is posttranslationally modified by protein kinases including protein kinase C (PKC) and cAMP-dependent kinase at the predicted phosphorylation sites at the "SRK, aa 7-9," "SVK, aa 11-13," "RKAS, aa 8-11," and "TKK, aa 21-23" (Johannessen et al, 2008;Sariyer et al, 2006). Agnoprotein also F I G U R E 3 The 3D structure of the full-length JC virus agnoprotein was recently resolved by NMR (Coric et al, 2017). According to this 3D structure, agnoprotein contains a minor and a major α-helix located at amino acid position Leu6-Lys13 and Arg24-Phe39, respectively.…”
Section: Functional Domains Of Agnoproteinmentioning
confidence: 99%
“…A recently solved NMR structure in organic solvent has revealed a second α-helix, albeit minor, spanning residues Leu6-Lys13 (Fig. 15.11) (Coric et al 2017).…”
Section: The Polyomavirus Jc Agnoproteinmentioning
confidence: 99%
“…It also interacts with cellular proteins, including the Y-box-binding factor 1 (YB-1) , tumor suppressor p53 (Darbinyan et al 2002), tubulin (Endo et al 2003), DNA damage repair protein Ku70 (Darbinyan et al 2004), fasciculation and elongation protein zeta 1 (FEZ1) , heterochromatin protein 1 alpha (HP-1α) , protein phosphatase 2A (PP2A) (Sariyer et al 2008), and the adaptor protein complex 3 (AP3) δ subunit (Suzuki et al 2013). Coric et al (2017)] One of the interesting host factors targeted by the JCV agnoprotein is the AP3 (Suzuki et al 2013). Interaction of agnoprotein with the δ subunit of AP3 (AP3D) appears to hijack the AP3-mediated intracellular vesicular trafficking to prevent the targeted lysosomal degradation of agnoprotein.…”
Section: Intraviral and Host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“… Agnoprotein (Agno) is an important regulatory protein of JC virus (JCV), BK virus (BKV) and simian virus 40 (SV40) and these viruses are unable to replicate efficiently in the absence of this protein. Recent 3D–NMR structural data revealed that Agno contains two alpha-helices (a minor and a major) while the rest of the protein adopts an unstructured conformation (Coric et al ., 2017, J Cell Biochem). Previously, release of the JCV Agno from the Agno-positive cells was reported.…”
mentioning
confidence: 99%